The Cambridge introduction to Harriet Beecher Stowe - Robbins, Sarah (Cambridge University, 2013)
Through the publication of her bestseller Uncle Tom's Cabin, Harriet Beecher Stowe became one of the most internationally famous and important authors in nineteenth-century America. Today, her reputation is more complex, and Uncle Tom's Cabin has been debated and analysed in many different ways. This book provides a summary of Stowe's life and her long career as a professional author, as well as an overview of her writings in several different genres. Synthesizing scholarship from a range of perspectives, the book positions Stowe's work within the larger framework of nineteenth-century culture and attitudes about race, slavery and the role of women in society. Sarah Robbins also offers reading suggestions for further study. This introduction provides students of Stowe with a richly informed and accessible introduction to this fascinating author.